2021
DOI: 10.1111/ppc.12946
|View full text |Cite
|
Sign up to set email alerts
|

Wounded healers during the COVID‐19 syndemic: Compassion fatigue and compassion satisfaction among nursing care providers in Greece

Abstract: Purpose The aim of this study was to investigate compassion fatigue (CF) and compassion satisfaction (CS) in nursing care providers in COVID‐19 units. Methods A mixed‐method study with 105 nurses. Results 23% of participants reported high CF risk while 77% expressed high to moderate potential for CS. Adequate preparation/education, clear and accountable leadership, and team sharing of feelings, experiences, and responsibilities during the transition in the COVID‐19 unit helped participants to deal with overwhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 35 publications
2
41
1
3
Order By: Relevance
“…Several nurses expressed a moral obligation and personal pride that they could care for COVID patients under such adverse conditions. This finding of professional obligation and self-esteem in being able to “answer the call” was consistent with prior studies on COVID nursing ( Bennett et al, 2020 ; Foli et al, 2021 ; Missouridou et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…Several nurses expressed a moral obligation and personal pride that they could care for COVID patients under such adverse conditions. This finding of professional obligation and self-esteem in being able to “answer the call” was consistent with prior studies on COVID nursing ( Bennett et al, 2020 ; Foli et al, 2021 ; Missouridou et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…This is evidence to show that nursing caregivers may feel a sense of satisfaction and sense of accomplishment as they overcome anxiety and fear experienced during COVID-19, a view echoing the result of a study among nursing care providers in Greece (Missouridou et al, 2021). Thus, the initial impact, engaging in empathetic relationship with COVID-19 patients may lead to opportunities for growth and appreciation of life (Missouridou et al, 2021). Nevertheless, as researchers recommend, there is need for recognition of personal loss history, unresolved issues and acceptance of personal limitations which is necessary for nursing care providers suffering from compassion fatigue (Missouridou, 2017).…”
Section: Discussionmentioning
confidence: 72%
“…However, 21.27% of the participants indicated that had low levels of compassion fatigue. This is evidence to show that nursing caregivers may feel a sense of satisfaction and sense of accomplishment as they overcome anxiety and fear experienced during COVID-19, a view echoing the result of a study among nursing care providers in Greece (Missouridou et al, 2021). Thus, the initial impact, engaging in empathetic relationship with COVID-19 patients may lead to opportunities for growth and appreciation of life (Missouridou et al, 2021).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This may have resulted from adequate education, clear and accountable leadership, responsibilities during the transition in the COVID-19 unit, thus, helping to cope with devastating anxiety. 18 …”
Section: Discussionmentioning
confidence: 99%